Systematic cultural adaptation of cognitive-behavioral therapy to reduce alcohol use among HIV-infected outpatients in western Kenya. - Papas, Rebecca K; Sidle, John E; Martino, Steve; Baliddawa, Joyce B; Songole, Rogers; Omolo, Otieno E; Gakinya, Benson N; Mwaniki, Michael M; Adina, Japheth O; Nafula, Tobista; Owino-Ong'or, Willis D; Bryant, Kendall J; et al. (AIDS and behavior, 2010)
Two-thirds of those with HIV worldwide live in sub-Saharan Africa. Alcohol use is associated with the HIV epidemic through risky sex and suboptimal ARV adherence. In western Kenya, hazardous drinking was reported by HIV (53%) and general medicine (68%) outpatients. Cognitive behavioral treatment (CBT) has demonstrated strong efficacy to reduce alcohol use. This article reports on a systematic cultural adaptation and pilot feasibility study of group paraprofessional-delivered CBT to reduce alcohol use among HIV-infected outpatients in Eldoret, Kenya. Following adaptation and counselor training, five pilot groups were run (n = 27). Overall attendance was 77%. Percent days abstinent from alcohol (PDA) before session 1 was 52-100% (women) and 21-36% (men), and by session 6 was 96-100% (women) and 89-100% (men). PDA effect sizes (Cohen's d) between first and last CBT session were 2.32 (women) and 2.64 (men). Participants reported treatment satisfaction. Results indicate feasibility, acceptability and preliminary efficacy for CBT in Kenya.
Keywords: Adult; Alcohol Drinking; Alcoholism; Cognitive Therapy; Counseling; Cultural Characteristics; Feasibility Studies; Female; HIV Infections; Humans; Kenya; Male; Middle Aged; Outpatients; Patient Acceptance of Health Care; Patient Satisfaction; Pilot Projects; Treatment Outcome